2000
DOI: 10.1094/mpmi.2000.13.12.1322
|View full text |Cite
|
Sign up to set email alerts
|

Xanthomonas oryzae pv. Oryzae Avirulence Genes Contribute Differently and Specifically to Pathogen Aggressiveness

Abstract: Genomic copies of three Xanthomonas oryzae pv. oryzae avirulence (avr) genes, avrXa7, avrXal0, and avrxa5, and four homologous genes, aB3.5, aB3.6, aB4.3, and aB4.5, were mutagenized individually or in combination to study the roles of avr genes in one component of pathogen fitness, i.e., aggressiveness or the amount of disease X. oryzae pv. oryzae causes in susceptible rice lines. These X. oryzae pv. oryzae genes are members of the highly related Xanthomonas avrBs3 gene family. Compared to the wild-type strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 29 publications
4
108
0
2
Order By: Relevance
“…The copy number of the 34 aa repeat unit of the AvrBs3 protein determines the specificity of recognition by the Bs3 resistance gene (Herbers et al, 1992), whereas in p25 protein it is determined by single amino acid changes ( Table 2) that influence known properties of p25 (Klein et al, 2007). Some members of the AvrBs3 family are involved in disease symptom formation (Swarup et al, 1992;Yang et al, 1996;Bai et al, 2000), and in those cases, the protein displays a virulence phenotype in one host, but not in other hosts. In contrast, p25 is responsible for the induction of rhizomania disease and clearly functions at the cultivar-specific level.…”
Section: Discussionmentioning
confidence: 99%
“…The copy number of the 34 aa repeat unit of the AvrBs3 protein determines the specificity of recognition by the Bs3 resistance gene (Herbers et al, 1992), whereas in p25 protein it is determined by single amino acid changes ( Table 2) that influence known properties of p25 (Klein et al, 2007). Some members of the AvrBs3 family are involved in disease symptom formation (Swarup et al, 1992;Yang et al, 1996;Bai et al, 2000), and in those cases, the protein displays a virulence phenotype in one host, but not in other hosts. In contrast, p25 is responsible for the induction of rhizomania disease and clearly functions at the cultivar-specific level.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no reports of natural mechanisms of how new avr genes or race differentiation are generated. Mutational analyses of avrBs3/ pth genes revealed that the order and type of repeats in the central domain were important for race-specificity or pathogen fitness 3,38,39 . In general, repetitive regions of DNA are known to be active sites for homologous recombination 28 .…”
Section: Fig 5 Conservation Of Xoo Genes In Xac and Xccmentioning
confidence: 99%
“…The RFLP-EcoRI analysis performed in this study may not detect changes in the copies of the avr genes that are causing a variation in the virulence patterns of the strains. Changes in the avr structure that cause a variation in the virulence pattern of the strain can be due to single mutations at the 3Ј terminus of the avrXa7 alleles (4,26). One strategy could be to sequence the copies of the plasmid-borne avr gene copies in the new pathotypes.…”
Section: Vol 70 2004 Xanthomonas Genetic Structure and Population Dmentioning
confidence: 99%